Decreasing capacity of jpeg2000 standard image on fpga board - Bach Tuan Dong; Ngo Thanh Dong; Nguyen Tuan Phuoc; Le My Ha (Journal of Technical Education Science, 2014)
In this paper, a method proposed to increase processing speed and reduce image capacity in JPEG2000 image standard. The selected region of interest (ROI) utilized to retain the important parts of the image and ignore the other regions. The advantages of this proposed method is: It can be performed 5 levels corresponding to the levels in FDWT. The bit width of image does not increase if it compared with the size of image entrancing ROI block. The quality of the background could reduce as requirement. The S + P method is chosen to divide the mask of ROI into many layers. The method selecting ROI in JPEG2000 standard is implemented on the hardware which supports many regions of interesting and different shapes. The experiment carried out on the FPGA to demonstrate the effectiveness of this proposed method.